Analisis Penerapan Balanced Scorecard Pada Kinerja Karyawan Bank BRI Unit Sokaraja Tengah - Julianti, Taliyah; Puspitaningrum, Devi; Hasna, Amelia Nilal; Shafrani, Yoiz Shofwa (Universitas Maritim AMNI Semarang, 2025)
This study aims to explore the implementation of the Balanced Scorecard (BSC) through the digital system